(untitled) - Trần, Kim Ngân (Cần Thơ, 2020)
Corrective feedback has been discussed mainly in second language acquisition contexts, but few have been done regarding corrective feedback in foreign language settings, including English. The present study examined teachers’ perceptions towards English corrective feedback in the context of English as a Foreign Language at some colleges in a local province of Vietnam. Furthermore, this thesis also identified the corrective feedback types used by the EFL college teachers. The questionnaire, interviews and classroom observations were used to collect the data. The major finding from the data on teachers’ perceptions indicated that teachers in general had a positive perception or attitude towards English oral corrective feedback. However, some considered it as optional since they were concerned with learners’ reactions and feelings when provided corrective feedback. A second major finding of the study was that elicitation was the most frequent type and metalinguistic feedback was favored next by the majority of the participants. These two types of oral corrective feedback were most frequently used. The next finding from this current research was the highlights of advantages and disadvantages which oral corrective feedback brought to a speaking class such as developing critical thinking abilities and destroying the self-esteem, inhibiting college students to develop their language in a natural way. The current study has provided insights into how English teachers might attend to their learners’ English learning needs, particularly by extending teachers’ use of oral corrective feedback. Pedagogical implications are made for further investigation into the use of oral corrective feedback in teaching EFL students.
Keywords: English language,Anh ngữ; Study and teaching,Dạy và học